FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN MAKANAN HALAL MELALUI GOFOOD SAAT COVID-19 - Adri 'Aunur Rahman (2021)
This study aims to find out and explain about the Factors That Affect Halal Food Consumers' Purchase Decision on GoFood during Covid-19. This research uses quantitative methods. The population is a community of GoFood service users in Jabodetabek during the Covid-19 pandemic. This research used primary data as a data source with a purposive sampling method for as many as 265 respondents. Data analysis using SmartPLS. This research shows that the presence of Halal label on the GoFood application significantly affect the consumers' decision making process of food purchasing on GoFood services. The quality of sharia-based services and contactless delivery should be implemented to amplify the convenience of consumers, the quality of sharia-based services have significant effect on the consumers' purchase decision. Usually, the price of products is one of the factors that affect consumers' purchase decision making process. However, many consumers prefer GoFood services to purchase the products during the Covid-19 pandemic, the price has no significant effect. The Researchers hope gofood users will benefit from the results of this research. that is to continue to develop halal labels and consumer convenience from halal labels and service quality. Limitations of this research include the lack of variables and the limited focus of research, in which the researcher only used 3 independent variables in this research, which only conducted in Greater Jabodetabek. Keywords: halal food, halal label, price, purchase decision, quality of service